Underwater Image Restoration Based on Illumination Normalization and Deblurring - Kumar, I. Jeya; Lenin Fred, A; Seldev Christopher, C (International Journal of Computer Sciences and Engineering, 2025)
The fundamental reason for submerged image handling is to enhance submerged image enhancement. The preparing of submerged image caught is essential in light of the fact that the nature of submerged images influence and these images drives some significant issues when contrasted with images from a clearer domain. Because of the presence of clean particles in the water, submerged images suffer from the backscattering impact. To overcome this drawback I propose the new method called illumination normalization and deblurring of underwater image restoration. In this paper propose, first estimate the illumination directions of underwater images and cope with the problem of illumination normalization. Secondly deblurring of the underwater image using deconvolution algorithm and finally by the fusing both the results the restored image is acquired.The quality of the enhanced image is evaluated by using the metric is called blind/reference less image spatial quality evaluator (BRISQUE).